Efektivitas Air Rebusan Sirih Merah (Piper crocatum) terhadap Penyembuhan Luka Perineum pada Ibu Post Partum di Praktik Mandiri Bidan Rica Merdekawaty Tahun 2023 - Wika Sepiwiryanti; Sartika Dwi Yolanda Putri; Yulia Yulia; Rica Merdekawaty (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2023)
The postpartum period (puerperium) is the period that begins after 2 hours postpartum and ends when the uterus returns to its pre-pregnancy state, lasting 6 weeks. The postpartum period is an important thing to pay attention to in order to reduce maternal mortality. Perineal rupture is a tear caused by spontaneous birth of a baby, either by using a tool or action. Perineal wound care is important to prevent infection of the reproductive organs, one method of perineal wound care is non-conventional therapy using red betel leaf (Piper crocatum) boiled water which contains flavonoids, alkaloids, polyphenolic compounds, tannins and essential oils which are known to has antibacterial activity. The purpose of this study was to determine the effectiveness of red betel (Piper crocatum) cooking water for perineal wound healing in postpartum mothers. This research is a quantitative study with a population of all postpartum mothers with perineal wounds at PMB Rica Merdekawaty with a total sample of 30 respondents consisting of the intervention group and the control group. The data that was collected was then analyzed using the chi square statistical test (p value = 0.029). Based on the chi square analysis, it showed that red betel leaf boiled water was effective in healing perineal wounds in postpartum mothers.